Relato de Experiência no Programa Residência Pedagógica - DUTRA, Giovane dos Santos (2022)
This Course Conclusion Work follows the structural configuration of the Normative Instruction Nº 01/2022 of the Pró-rectory of Graduation of the Universidade Federal do Pará, which establishes the norms for TCC activities, made more flexible due to the consequences of the COVID-19 pandemic. Therefore, the Final Report submitted to CAPES will be used as a requirement for analysis by the reviewers of this text. This production is configured as a report of significant experiences lived in the scope of the Pedagogical Residency Program throughout the 18 months of permanence as a resident. In short, the textual production will address the difficulties experienced in teaching in the remote modality and adaptations to this new context, the use of digital platforms such as Google Classroom, Google Meet, and Wordwall. As a conclusion, the entry into the remote teaching format allowed for a glimpse of the challenges that emerge during the teaching trajectory, from the immersion in an atypical teaching context, which required a readjustment in the vision and practice of teaching, where it was necessary to resort to new ways of passing on knowledge and methodologies that would enable greater interaction with students and facilitate teaching and learning.